Relationship between the gut microbiota and temperament in children 1–2 years old in Chinese birth cohort. (April 2022) - Xie, Tianqu; Wang, Yuchen; Zou, Zhijie; Wu, Yinyin; Fan, Xiaoxiao; Dai, Jiamiao; Liu, Yanqun; Bai, Jinbing
Abstract: Background: Understanding the relationship between the gut microbiota and temperament can provide new insights for the regulation of behavioral intervention in children, which is still lacking research. This study aimed to examine the relationship between the gut microbiota and temperament in a cohort of children in 1 year and 2 years old. Methods: This study included a total of 37 children with completed information, in which 51 samples at age 1 and 41 samples at age 2 were received respectively. We collected birth and demographic information. Parents reported their child's temperament characteristics using the Infant Behavior Questionnaire-revised (IBQ-R) and Early Childhood Behavior Questionnaire (ECBQ). Fecal samples were collected from each child at 1 and 2 years old and sequenced with MiSeq sequencer. Multiple linear regressions and linear mixed effect models were used to analyze the relationship between the temperament and their microbiota composition as well as the diversity and effect of gender or age on this relationship. Results: At age of year 2, Faecalibacterium was negatively associated with high-intensity pleasure and surgency. Bifidobacterium was negatively correlated with Perceptual sensitivity. Results showed no difference about three domains between year 1 and year 2, while gut microbiota showed diversity difference and genera difference. There was no gender and age difference on the relationship between temperament and the gut microbiota. Conclusions: Temperament was associated with the gut microbiota over time. The temperament remained stable and the relationship between the gut microbiota and temperament wasn't associated with age and gender. Highlights: It is first study to explore the relationship between gut microbiota and temperament longitudinally. Temperament remains stable at first 1–2 year of life. Early temperament was correlated with the composition and diversity of gut microbiota.